Dietary factors affecting tissue profiles of long chain polyunsaturated fatty acids in cattle - Alvarado-Gilis, Christian A. (Kansas State University, 2014)
The main goal of this dissertation was to evaluate different methods to protect polyunsaturated fatty acids (PUFA) against biohydrogenation by ruminal microorganisms. The first chapter is a review of literature pertaining to fat and fatty acid metabolism by ruminants and why these fats are relevant in human nutrition. The second chapter discusses effects of supplementing high concentrations of dietary copper to feedlot cattle to assess impact on PUFA profiles in tissues. Two levels of copper (10 or 100 mg/kg) were supplemented to diets with or without flaxseed during the finishing period for beef heifers. Added copper did not affect performance (P > 0.15). Final body weights were similar for cattle fed with or without flaxseed (P > 0.05), but cattle fed diets with flaxseed consumed less feed (P < 0.05), and therefore were more efficient (P < 0.01). Carcass traits were unaffected by treatment. Feeding elevated levels of copper did not appreciably alter proportions of PUFA in plasma, but plasma concentrations of omega-3 fatty acids were greater for heifers fed flaxseed (P < 0.05). Chapter 3 describes the evaluation of 3 novel methods to protect PUFA from microbial biohydrogenation activity within the rumen, including a) coextrusion of flaxseed with molasses; b) mixing with soybean meal followed by induction of a non-enzymatic browning reaction; and c) encapsulation of ground flaxseed within a matrix consisting of dolomitic lime hydrate (L-Flaxseed). The resulting products were evaluated using in vitro methods to estimate resistance to biohydrogenation or in 12- to 14-d feeding studies in which plasma concentrations of [alpha]-linolenic acid (ALA) were measured. Our processing strategies a) and b) did not improve efficiency of omega-3 fatty acid utilization (P > 0.1). The in situ study of L-flaxseed revealed a 2-fold increase in resistance of ALA to ruminal biohydrogenation, and the concentration in plasma after 14 d on feed was more than 4 times that observed in cattle fed ground flaxseed, suggesting the dolomitic lime hydrate was effective as a protective matrix. Chapter 4 evaluated performance, carcass traits, and meat quality of finishing beef heifers in response to feeding diets containing L-Flaxseed. Animals were blocked by weight, randomly assigned to individual pens, and pens to 6 dietary treatments: Control (high concentrate finishing diet), ground flaxseed fed at 3 or 6% of diet DM, L-Flaxseed fed at 2, 4, or 6%. Concentration of ALA in meat increased linearly in response to the level of flaxseed fed (P < 0.05); Moreover, transfer of dietary ALA to tissues increased by 47% when flaxseed was encapsulated within the dolomitic lime matrix. Cattle that were fed diets with 4 or 6% L-Flaxseed consumed less feed than other treatments (P < 0.05), which adversely affected feedlot performance and carcass traits.
Keywords: Omega-3 fatty acids; Flaxseed; Copper; Protection; Biohydrogenation; Encapsulation; Agriculture, General (0473)